Religiosity of the Traditional Nasok Pare (Rice Planting) Community of the Dayak Paser Muluy in Gunung Lumut, East Kalimantan - Rif'ah Rif'ah; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This research aims to understand the religiosity of the traditional community of Nasok Pare (rice planting) Dayak Paser Muluy Gunung Lumut East Kalimantan. The research method used is qualitative with an ethnographic approach. The results show that the Nasok Pare (rice planting) ritual is an important part of the religiosity of the Dayak Paser Muluy community, which has deep spiritual and social meanings. The ritual serves as a symbol of fertility and prosperity, and strengthens community identity. This research also shows that modernization and social change can threaten the religiosity of traditional communities, so efforts are needed to preserve and develop the Nasok Pare (rice planting) ritual as part of Indonesia's cultural heritage.